Public Elementary School Bumi Agung Lampung Students' Perceptions About Maloclusions and The Need for Orthodontic Treatment - Krisnawati Krisnawati; Retno Widayati; Muhammad Sulaiman Kusumah Adiwirya; Benny Mulyono Soegiharto; Widya Kusumadewy; Dwita Pratiwi (Indonesian Dental Association, 2024)
Introduction: Based on Indonesia Basic Health Research in 2018, it is known that 47% of Lampung people experience tooth decay and only 51% of them regularly go to the dentist. The need for orthodontic treatment is quite high among students. Epidemiological studies in Japan show that around 40% of teenagers aged 15-18 years need orthodontic treatment, 27%-36% in England aged 10-15 years, while in South Jakarta (2004) is 48.5%. Brook and Shaw introduced the Index of Orthodontic Treatment Need (IOTN), to assess the need for orthodontic treatment in England. IOTN has been applied by Agusni, T to measure the treatment needs of urban and rural children in Surabaya. Objective: Aims to determine the perceptions of elementary school students in Lampung regarding Malocclusion and the need for Orthodontic treatment. Method: A cross-sectional study was conducted in May 2023, carried out on students at public Elementary School Bumi Agung who met the inclusion criteria, namely aged 9-13 years, had never and were not currently undergoing orthodontic treatment, and were willing to take part in the research. 130 people were selected using a purposive sampling technique. Questionnaires were used to obtain sociodemographic data and general knowledge about Dental and Oral Health and Malocclusion. Assessment of the need for orthodontic treatment was carried out using the AC IOTN by the subject and operator. Results: 90% of students answered the questionnaire correctly, and 42% of students needed orthodontic treatment. A Pearson Chi-Square analysis test was carried out and found that there was a statistical difference in the perception of the need for orthodontic treatment by students and operators (p-value <0.05). Conclusion: Students at SDN Bumi Agung, Kalianda, Lampung, have very good general knowledge about Dental and Oral Health and Malocclusion. However, this is unsubstantiated by the perception of the need for orthodontic treatment.